2017
DOI: 10.1371/journal.pone.0173474
|View full text |Cite
|
Sign up to set email alerts
|

Organic cation transporter 1 (OCT1) is involved in pentamidine transport at the human and mouse blood-brain barrier (BBB)

Abstract: Pentamidine is an effective trypanocidal drug used against stage 1 Human African Trypanosomiasis (HAT). At the blood-brain barrier (BBB), it accumulates inside the endothelial cells but has limited entry into the brain. This study examined transporters involved in pentamidine transport at the human and mouse BBB using hCMEC/D3 and bEnd.3 cell lines, respectively. Results revealed that both cell lines expressed the organic cation transporters (OCT1, OCT2 and OCT3), however, P-gp was only expressed in hCMEC/D3 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 56 publications
5
43
0
Order By: Relevance
“…lysozyme) (Schwake et al 2013). OCT1, OCT2 and 3 have been shown to be expressed in hCMEC/D3 and b.End3 cells in an earlier study by our group(Sekhar et al 2017) and OCTN1 and OCTN2 were shown to be expressed in both cell lines in this present study.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…lysozyme) (Schwake et al 2013). OCT1, OCT2 and 3 have been shown to be expressed in hCMEC/D3 and b.End3 cells in an earlier study by our group(Sekhar et al 2017) and OCTN1 and OCTN2 were shown to be expressed in both cell lines in this present study.…”
Section: Discussionsupporting
confidence: 76%
“…They are not listed on the misidentified cell line register (version 9 released 14 th October 2018). Both cell lines require different cell mediums to grow to confluence and their BBB phenotype has been confirmed using Western blots, confocal and transmission electron microscopy (Sekhar et al 2017)(section 4.10). Functional expression of several transporters has also been demonstrated by our group(Sekhar et al 2017)(Watson et al 2016)(Watson et al 2012).…”
Section: Methodsmentioning
confidence: 92%
See 3 more Smart Citations